Unprecedented ROMP Activity of Low-Valent Rhenium-Nitrosyl Complexes: Mechanistic Evaluation of an Electrophilic Olefin Metathesis System - Frech, Christian M.; Blacque, Olivier; Schmalle, Helmut W.; Berke, Heinz; Adlhart, Christian; Chen, Peter (Chemistry : a European journal, 2006)
The reaction of [Re(H)(NO)2(PR3)2] complexes (1 a: R = PCy3; 1 b: R = PiPr3) with [H(OEt2)2][BArF4] ([BArF4] = tetrakis{3,5‐bis(trifluoromethyl)phenyl}borate) in benzene at room temperature gave the corresponding cations [Re(NO)2(PR3)2][BArF4] (2 a and 2 b). The addition of phenyldiazomethane to benzene solutions of 2 a and 2 b afforded the moderately stable cationic rhenium(I)‐benzylidene‐dinitrosyl‐bis(trialkyl)phosphine complexes 3 a and 3 b as [BArF4]− salts in good yields. The complexes 2 a and 2 b catalyze the ring‐opening metathesis polymerization (ROMP) of highly strained nonfunctionalized cyclic olefins to give polymers with relatively high polydispersity indices, high molecular weights and over 80 % Z configuration of the double bonds in the chain backbone. However, these complexes do not show metathesis activity with acyclic olefins. The benzylidene derivatives 3 a and 3 b are almost inactive in ROMP catalysis with norbornene and in olefin metathesis. NMR experiments gave the first hints of the initial formation of carbene complexes from [Re(NO)2(PR3)2][BArF4] (2 a and 2 b) and norbornene. In a detailed mechanistic study ESI‐MS/MS measurements provided further evidence that the carbene formation is initiated by a unique reaction sequence where the cleavage of the strained olefinic bond starts with phosphine migration forming a cyclic ylide–carbene complex, capable of undergoing metathesis with alternating rhenacyclobutane formation and cycloreversion reactions (“ylide” route). However, even at an early stage the ROMP propagation route is expected to merge into an “iminate” route by attack by the ylide function on one of the NNO atoms followed by phosphine oxide elimination. The formation of phosphine oxide was confirmed by NMR spectroscopy. The proposed mechanism is supported further by detailed DFT calculations. A unique catalytic mechanism operates as illustrated to form the initiating carbene complex when stable low‐valent [Re(NO)2(PR3)2]+ cations catalyze the unprecedented ROMP of strained nonfunctionalized olefins. This yields high‐molecular‐weight polymers with predominantly Z‐olefinic content.